MAIN FEATURES OF THE HUNGARIAN SANCTION SYSTEM - Juhász, Zsuzsanna (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
Abstract: The aim of this study is to illustrate the main features of the Hungarian system of criminal sanctions and to focus on some problematic issues of the current sanction system in relation to fix-term imprisonment and life imprisonment and also the punitive nature of criminal law.
Keywords: Keywords: criminal sanction system, fix-term imprisonment, life imprisonment, recidivist, punitive criminal law